HMLP,MLP and Recurrent Networks for Carbon Monoxide Concentrations Forecasting: A Comparison Studies. - Raji, Usharani; Mashor, M.Y.; Ali, A.N.; Adom, A.H.; Sadullah, A.F. (2005)

(untitled)
Carbon Monoxide (CO) is a primary pollutant in urban area, due to the major emission from motor vehicles. Forecasting of CO or other gas pollutants concentration are very important since preventive action can be taken if the forecasted CO level exceeds certain value.